AUGMENTED REALITY PENGENALAN JENIS HEWAN MAMALIA MENGGUNAKAN METODE MARKER BASED TRACKING (Studi Kasus : SDN Putat Nutug 01) - Muhammad Rifky Fareza; Raditia Vindua (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Technology is used by humans in various fields to help complete activities that were once done manually. By utilizing technology, these activities can be completed easily and quickly. The technology that is currently developing is Augmented Reality (AR) because of its attractive visual appearance so that it can display 3-dimensional objects and their animations and look like they exist in the real world. Therefore, AR can be used for mammalian animal recognition. Currently for the introduction of mammalian animals can only be learned from books, videos, and the internet. So, in this study built AR applications for the introduction of mammals are accompanied by sound so that the information conveyed in more detail. To build applications based on android, Unity is used while the creation of AR applications used Vuforia SDK. Markers are found on a book to display 3D object visualization. Applications built on the android operating system by applying Augmented Reality technology aims to the introduction of mammals to elementary school children who can add visualization of 3D objects into the real environment so that they can get to know the mammals. Based on the results of testing the ideal distance, the more visible pixels on the marker, the more influential on the system to display 3D objects. Based on the results of testing validity, children can recognize mammals by using the application AR introduction of mammals with the results of 83,06% of respondents answered very well. Therefore, this mammal recognition AR application can be used by users as a medium to get to know mammals.